2010
DOI: 10.3856/vol38-issue1-fulltext-8
|View full text |Cite
|
Sign up to set email alerts
|

From fresh water to the slope: fish community ecology in the Rio de la Plata and the sea beyond

Abstract: ABSTRACT. The spatial pattern of fish assemblages and its relationship with factors along an environment gradient, from fresh to marine water environment along the Río de la Plata estuary (36ºS, 56ºW) the shelf and part of the slope, was examined using data from 22 sampling stations. Fish were sampled from all station with an Engel type trawl (200 mm stretched mesh in the wings, 120 mm stretched mesh in the cod ends, 4 m vertical opening and 15 m horizontal aperture) towed at 4 knots for 20 to 30 min per set. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 29 publications
(35 reference statements)
0
19
0
1
Order By: Relevance
“…For example, of the major North Sea fish families (e.g., Daan et al ), carbonate polymorphs can be predicted only for the Pleuronectidae (righteye flounders) and Carangidae; other families, including the Gadidae (codfishes), Clupeidae (herrings and sardines), Scombridae (tunas and mackerels), and Ammoditydae (sandlances) remain unrepresented. Similarly, of the important Patagonian Shelf fish families (e.g., García et al ), products can be predicted only for the Carangidae; the Merlucciidae (hakes), Percophidae (duckbills), and Congridae (conger eels) being among those that are unrepresented. These high latitude fish communities thus represent an obvious target for future research—particularly given their importance in the fisheries industry (e.g., Watson ) and the consequent potential for their overexploitation to result in shifts in carbonate production regimes (Salter et al ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, of the major North Sea fish families (e.g., Daan et al ), carbonate polymorphs can be predicted only for the Pleuronectidae (righteye flounders) and Carangidae; other families, including the Gadidae (codfishes), Clupeidae (herrings and sardines), Scombridae (tunas and mackerels), and Ammoditydae (sandlances) remain unrepresented. Similarly, of the important Patagonian Shelf fish families (e.g., García et al ), products can be predicted only for the Carangidae; the Merlucciidae (hakes), Percophidae (duckbills), and Congridae (conger eels) being among those that are unrepresented. These high latitude fish communities thus represent an obvious target for future research—particularly given their importance in the fisheries industry (e.g., Watson ) and the consequent potential for their overexploitation to result in shifts in carbonate production regimes (Salter et al ).…”
Section: Discussionmentioning
confidence: 99%
“…These transition zones were not static but expanded and contracted between the seasons and were driven primarily by salinity. A later trawl study covering the freshwater to marine environment of the Río de la Plata system showed that the fish community could be divided into four assemblages along the riverine-marine gradient, namely riverine, estuarine, shelf and slope assemblage (Garcia et al, 2010). According to these authors, bottom salinity and temperature were the primary environmental variables driving the differences in fish assemblage structure between the four identified areas.…”
Section: Salinitymentioning
confidence: 99%
“…At La Plata River (AR), L. grossidens is frequent and abundant in the riverine portion of the estuary, near the estuarine area (García et al 2010). In the Patos Lagoon Estuary, the species occurs throughout the year (Buckup 1984, Chao et al 1985, Ramos 2005, and was among the ten most abundant species of shallow waters , bottom trawl (Vieira 2006) and dominated the pelagic assemblage (Vieira & Castello 1997).…”
Section: Estuarine Populationsmentioning
confidence: 99%